Online Activism Through Social Media Engagement of Community Youth Leaders from a Teachers College - Quimba, Chris Gem; Pilarta, Jorlyn; Luengas, Donn Krisry; Pedroso, John Erwin (RADINKA JAYA UTAMA PUBLISHER, 2025)
Social media has continuously emerged as a transformative platform for youth civic engagement, enabling young leaders to participate in public discourse, advocate for causes, and shape community narratives. The aim of this study is examine how Filipino community youth leaders, specifically Sangguniang Kabataan (SK) Chairpersons, approach their social media engagement in relation to online activism. Employing a qualitative narrative inquiry approach grounded in Social Constructionism, this research captures the lived experiences of student leaders from a teachers' college. A semi-structured interview guide distributed through Google Forms was used to collect data through written interviews, enabling participants to provide in-depth, reflective answers. Findings reveal three major themes: (1) Crafting an Online Identity, where digital spaces allow for both personal self-expression and public image building; (2) Reimagining Activism Online, wherein social media actions become meaningful forms of civic participation; and (3) Developing Purpose in Activism, highlighting how pivotal events, emotional connections, and leadership roles deepen commitment to advocacy. These themes highlight how social media engagements strongly influence the political activities of community youth leaders, thus encouraging them to engage in digital forms of activism. These findings demonstrate that youth engagement online can evolve into reflective and sustained activism, underlining the role of social media as both a platform and a catalyst for youth-driven civic leadership in the digital age.